Astragalin Attenuates Dextran Sulfate Sodium (DSS)-Induced Acute Experimental Colitis by Alleviating Gut Microbiota Dysbiosis and Inhibiting NF-κB Activation in Mice - Peng, Lei; Gao, Xiaoyu; Nie, Long; Xie, Jing; Dai, Tianyi; Shi, Chongying; Tao, Liang; Wang, Yan; Tian, Yang; Sheng, Jun (Frontiers in Immunology, 2020)
With the UC incidence increasing worldwide, it is of great importance to prevent and treat UC. However, efficient treatment options for UC are relatively limited. Due to the potentially serious adverse effects of existing drugs, there is an increasing demand for alternative candidate resources from natural and functional foods. Astragalin (AG) is a type of anti-inflammatory flavonoid, with Moringa oleifera and Cassia alata being its main source. In this study, we investigated the therapeutic effects of AG in mice with dextran sulfate sodium (DSS)-induced colitis. Our results suggested that AG treatment reduced the weight loss and disease activity index (DAI), prevented colon shortening and alleviated colonic tissue damage. AG treatment reduced the expression of proinflammatory cytokines and related mRNAs (such as TNF-α, IL-6 and IL-1β), inhibited the colonic infiltration of macrophages and neutrophils, ameliorated metabolic endotoxemia, and improved intestinal mucosal barrier function (expression levels of mRNAs such as ZO-1, occludin and Muc2 were increased). Western blotting analysis revealed that AG downregulated the NF-κB signaling pathway. Moreover, AG treatment partially reversed the alteration of gut microbiota in the colitic mice mainly by increasing the abundance of potentially beneficial bacteria (such as Ruminococcaceae) and decreasing the abundance of potentially harmful bacteria (such as Escherichia-Shigella). Ruminococcaceae and Enterobacteriaceae (Escherichia-Shigella) were thought to be the key groups for AG to improve UC. Therefore, AG might exert a good anti-UC effect through Microbiota/LPS/TLR4/NF-kB-related pathways in mice. The results of this study revealed the anti-inflammatory effect and mechanism of AG and provide an important reference for studying the mechanism of natural flavonoids in preventing inflammation-driven diseases.